Project management survival a practical guide to leading, managing & delivering challenging projects - Jones, Richard, 1964- (Gale virtual reference library, 2007)
Offers practical advice on getting to the truth of a project, getting the right initial plan, developing a genuinely workable plan, and managing people so the project stays on track.